Transient congenital hyperinsulinism and hemolytic disease of a newborn despite rhesus D prophylaxis: a case report - Sandra Simony Tornoe Riis (BMC, 2021)
Abstract Background In neonates, rhesus D alloimmunization despite anti-D immunoglobulin prophylaxis is rare and often unexplained. Rhesus D alloimmunization can lead to hemolytic disease of the newborn with anemia and unconjugated hyperbilirubinemia. In past reports, transient congenital hyperinsulinism has been described as a rare complication of rhesus D alloimmunization. Our case report illustrates that rhesus D alloimmunization can result in a pseudosyndrome with severe congenital hyperinsulinism, anemia, and conjugated hyperbilirubinemia, despite correctly administered anti-D immunoglobulin prophylaxis. Case presentation We report of a 36-year-old, Caucasian gravida 1, para 1 mother with A RhD negative blood type who received routine antenatal anti-D immunoglobulin prophylaxis. Her full term newborn boy presented with severe congenital hyperinsulinism, anemia, and conjugated hyperbilirubinemia up to 295 µmol/L (ref. < 9), accounting for 64% of the total bilirubin. Syndromic congenital hyperinsulinism was suspected. Examinations showed a positive direct antiglobulin test, initially interpreted as caused by irregular antibodies; diffuse congenital hyperinsulinism by 18F-DOPA positron emission tomography/computed tomography scan; normal genetic analyses for congenital hyperinsulinism; mildly elevated liver enzymes; delayed, but present bile excretion by Tc99m-hepatobiliary iminodiacetic acid scintigraphy; and cholestasis and mild fibrosis by liver biopsy. The maternal anti-D titer was 1:16,000 day 20 postpartum. Y-chromosome material in the mother’s blood could not be identified. This could, however, not exclude late intrapartum fetomaternal hemorrhage as the cause of immunization. No causative genetic findings were deetrmined by trio whole exome sequencing. The child went into clinical remission after 5.5 months. Conclusion Our case demonstrates that rhesus D alloimmunization may present as a pseudosyndrome with transient congenital hyperinsulinism, anemia, and inspissated bile syndrome with conjugated hyperbilirubinaemia, despite anti-D immunoglobulin prophylaxis, possibly due to late fetomaternal hemorrhage.